The increasing significance of impact within the Research Excellence Framework (REF). (October 2020) - Sutton, E.
Abstract: Introduction: The UK's Research Excellence Framework (REF) is a performance-based research funding system that was introduced in 2014. REF is a process of expert review in universities which assesses the quality and reach of research across higher education. It highlights areas of excellence, benchmarks the quality of previously funded research and provides accountability for ongoing public investment in research. In addition to assessing the quality of research outputs and the environment in which research is undertaken, the REF became the first exercise to evaluate the impact of research outside of academia. Discussion: This article specifically addresses the impact component of the REF, explaining what is understood by the term 'impact' and considering how impact is gaining significance within the REF framework as a measure of research excellence. It also reflects on the complexities of measuring impact and ongoing resistance from academics to the impact agenda, which they believe threatens academic freedom and appears only to value research that generates specific outcomes. In order to address these and other issues arising from the first-ever assessment of impact in REF 2014, institutions were consulted on the proposed guidance for the REF 2021 submission. Conclusion: The final REF 2021 guidance has sought to provide clearer detail on interpretations of impact and its underpinning research in order to reassure researchers that their academic freedom will not come under threat. However, this process still fails to capture other impactful research being undertaken across institutions, which falls outside of the strict REF criteria.